2012
DOI: 10.1590/s0103-84782012005000006
|View full text |Cite
|
Sign up to set email alerts
|

Enxertia interespecífica de jabuticabeira: influência do tipo de garfo

Abstract: Este trabalho objetivou avaliar o pegamento e desenvolvimento dos enxertos de duas espécies de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
5
1
2
Order By: Relevance
“…A wide range of graft fixation levels has been reported for other Myrtaceae family species, such as 20, 40, and 50%, for jabuticaba (Plinia cauliflora), pitanga (Eugenia uniflora) and camu-camu (Myrciaria dubia), respectively (Lattuada et al, 2010;Malagi et al, 2012). This variation is also observed within the same species, as reported by Franco et al (2010) for jabuticaba-sabará [Plinia jaboticaba (Vell.)…”
Section: Resultsmentioning
confidence: 58%
“…A wide range of graft fixation levels has been reported for other Myrtaceae family species, such as 20, 40, and 50%, for jabuticaba (Plinia cauliflora), pitanga (Eugenia uniflora) and camu-camu (Myrciaria dubia), respectively (Lattuada et al, 2010;Malagi et al, 2012). This variation is also observed within the same species, as reported by Franco et al (2010) for jabuticaba-sabará [Plinia jaboticaba (Vell.)…”
Section: Resultsmentioning
confidence: 58%
“…An average length of 8.41cm was obtained for primary buds in the union between jabuticabeiras (Table 2) onto Hybrid jabuticabeira (rootstock) (5.47 and 0.28cm, respectively), in which both combinations were grafted using the cleft grafting technique. MALAGI et al(2012) obtained a mean bud length of 11.1cm for combinations between species of jabuticabeira Açu. The increased length obtained for the same species combination, when compared with the results obtained in the present study, could be related to the lower number of buds obtained in the previous study, which may have increased the amount of resources available per bud and consequently their increased growth.…”
Section: Resultsmentioning
confidence: 95%
“…Similar results were obtained by SASSO et al (2010), who reported 2.2 and 2.3 buds for grafts onto the same species during two separate grafting seasons (May and August, respectively). Additionally, 2.06 buds per grafted plant were obtained by MALAGI et al(2012), who used the same jabuticabeira species as scion and rootstock.…”
Section: Resultsmentioning
confidence: 99%
“…De fato, as garfagens realizadas em porta-enxertos com seis e oito meses de idade, e diâmetro médio de 20 e 25 mm, respectivamente, também apresentaram baixas porcentagens de sobrevivência dos enxertos aos 90 dias após a enxertia (Tabela 3). Malagi et al (2012) ressaltaram que garfos semilenhosos de maior diâmetro, devido ao seu estado de maior lignificação, contribuem para a redução do pegamento dos enxertos; além disso, à medida que as plantas lenhosas jovens se desenvolvem, a lignificação do caule aumenta, de modo que o sucesso da enxertia é limitado pela dificuldade de cicatrização e pela união cambial do enxerto e do porta-enxerto.…”
Section: Resultsunclassified